Knowledge and psychosocial wellbeing of nurses caring for people living with HIV/AIDS (PLWH) - Lufuno Makhado; Mashudu Davhana-Maselesele (AOSIS, 2016)
The challenges of caring for people living with HIV (PLWH) in a low-resource setting has had a negative impact on the nursing profession, resulting in a shortage of skilled nurses. In response to this shortage and perceived negative impact, we conducted a descriptive, cross-sectional study to describe the level of knowledge and psychosocial wellbeing of nurses caring for PLWH at a regional hospital in Limpopo Province, South Africa. A total of 233 nurses, the majority being female, participated and were stratified into professional nurses (n =108), enrolled nurses (n = 58) and enrolled nursing auxiliaries (n = 66). Data were collected using HIV/AIDS knowledge questionnaire, Maslach Burnout Inventory; AIDS Impact Scale and Beck's Depression Inventory. The total knowledge score obtained by all the participants ranged from 2 to 16, with an average of 12.93 (SD = 1.92) on HIV/AIDS knowledge. Depersonalization (D) (83.7%) and emotional exhaustion (EE) (53.2%) were reported among participating nurses caring for PLWH. Burnout was higher among professional nurses as compared to both enrolled nurses and enrolled nursing auxiliaries. There was a moderate negative significant correlation between HIV knowledge with the nurses' emotional exhaustion (r = 0.592), depression (r = 0.584) and stigma and discrimination (r = 0.637). A moderate to high level of burnout was evident among all levels of nurses. These findings lead to the recommendations for support of nurses caring for PLWH that include structured nursing educational support, organisational support with respect to employee wellness programmes that address depression and work burnout, as well as social support. The provision of these support mechanisms has the potential of creating a positive practice environment for nurses in the Vhembe District of the Limpopo Province in particular, and South Africa in general, and in improved care for PLWH.